Student voice research as a technology of reform in neoliberal times. (15th March 2021) - Nelson, Emily; Charteris, Jennifer
ABSTRACT: Calls for educators to promote student voice and agency in classrooms often overlook the importance of the policy milieu in which teaching and learning is performed. In this article we interrogate the constitution of student, teacher and researcher subjectivities within student voice research. Working with Stephen Ball's neoliberal technologies of reform (technologies of the market and performativity (including technologies of the self); implemented through acculturation), we take up the notion that those of us working in education are complicit in the reforms we work to disrupt and conceptualise research as a technology of reform. We analyse performativity mechanisms at play in our student voice research that produced students, teachers and researchers as neoliberal policy subjects even whilst working toward the democratic intent of student voice. We contribute a heuristic with which scholars and educators can interrogate technologies of reform at work in their student voice work.